2021
DOI: 10.1071/hc20070
|View full text |Cite
|
Sign up to set email alerts
|

VeCHAT: a proof-of-concept study on screening and managing veterans’ mental health and wellbeing

Abstract: INTRODUCTIONNew Zealand veterans may have complex mental and physical complaints related to multiple exposures to war environments. They are entitled to, but often do not, access a range of physical, mental health and social services funded through Veterans’ Affairs New Zealand. eCHAT (electronic Case-finding and Help Assessment Tool) is a self-completed electronic holistic screen for substance misuse, problem gambling, anger control, physical inactivity, depression, anxiety, exposure to abuse; and assesses wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“… Testing of online eCHAT tool in primary care Goodyear-Smith et al, 2013 In sample of 196 patients: 97% found iPad-based eCHAT easy to use; 9% had concerns about data privacy. Testing of CHAT tool in veteran health care Goodyear-Smith et al, 2021 In a sample of 34: VeCHAT tool proved acceptable to veterans and Veterans’ Affairs staff Feasibility study of the CHAT Elley et al, 2014 In sample of 107: CHAT found to be acceptable. 2 objections to alcohol questions; no other objections recorded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Testing of online eCHAT tool in primary care Goodyear-Smith et al, 2013 In sample of 196 patients: 97% found iPad-based eCHAT easy to use; 9% had concerns about data privacy. Testing of CHAT tool in veteran health care Goodyear-Smith et al, 2021 In a sample of 34: VeCHAT tool proved acceptable to veterans and Veterans’ Affairs staff Feasibility study of the CHAT Elley et al, 2014 In sample of 107: CHAT found to be acceptable. 2 objections to alcohol questions; no other objections recorded.…”
Section: Resultsmentioning
confidence: 99%
“…These tools screened for both substance use and gambling in either a treatment setting (Christo et al, 2003 ; and Denis et al, 2016 ) or in the general population (MacLaren & Best, 2010 ; and Schluter et al, 2018 ). The remaining 4 tools screened for risk factors across a diverse range of health concerns including substance use and gambling in a primary health setting (Goodyear-Smith et al, 2004 , 2009 , 2013 , 2021 ; and Elley et al,. 2014 ) or for underlying behavioral traits in the general population (Chamberlain & Grant, 2018 ; Guo et al, 2017 ; and Rockloff and Dyer, 2006 ).…”
Section: Resultsmentioning
confidence: 99%